Resource use and Productivity in Dryland Agriculture in Nagaur District (RAJASTHAN) - Vyas, D L (Annals of Arid Zone, 2025)
Resource use and productivity in dryland agriculture in Nagaur district of arid Rajasthan was examined for 1977-78 to 1979-80 for three faron size groups by employing production function approach. All the components of input-mix, excepting human labour, need additive adjustment for enhancement of value productivity of crop output-mix on dryland farms.